Senile asthenia as a predictor of the severity of the perioperative period in elderly and senile patients - M. B. Danyliuk; S. M. Zavhorodnii; A. I. Rylov; M. A. Kubrak; I. V. Pertsov (Patologìâ)
The aim. To evaluate the effectiveness of the diagnosis of senile asthenia using the Edmonton Frail scale in emergency abdominal surgery and to determine its impact on the severity of the perioperative period.